Driving Benefits of Virtual Reality in Cerebral Palsy: a narrative review - de Oliveira, Rebeca C. L.; Cardoso, Priscila S.; Almeida, Ingridi M. B.; da Silva, Francisco J. S.; Melo-Figueiredo, Leissa da S.; de Oliveira, Bruno B. M.; de Sá-Caputo, Danúbia da C.; Paineiras-Domingos, Laisa L. (Brazilian Journal of Health and Biomedical Sciences, 2021)
Introduction: Chronic childhood encephalopathy (CCE), still called cerebral palsy worldwide, is defined as a set of motor disorders caused by non-progressive disorders of the central nervous system, resulting in changes in muscle tone and posture. These changes are established in the pre, peri or postnatal period and numerous physical therapy modalities have been suggested for the management of these changes. Virtual reality (VR) has been used as an innovative therapeutic tool, with a motor approach that involves the individual and a computerized interaction field, with the simulation of exercises capable of stimulating movements in real time, motivation and sensory feedback. Objective: To evaluate the motor benefits of VR as a therapeutic modality in childrenwith CCE. Materials and methods: A narrative review was carried out, with articles found in the Bireme database (BVS) and in the virtual library Scientific Eletronic Library Online (SciELO). The descriptors used were: physiotherapy, virtual reality, children and CCE. Results: Only five articles were selected. Conclusion: The articles consulted suggest that the use of VR influences the improvement mainly of the child’s balance, helping kinesiotherapeutic treatment. However, with a small number of publications focused on the pediatric physiotherapeutic approach through VR, further studies are needed for better scientific proof of this tool.